Discrete mathematical structures - Chauhan, J. P (Krishna Prakashan Media, 2011)
Discrete mathematical structures / Chauhan, J. P. -- Meerut: Krishna Prakashan Media, 2011 511.3 C497e2 2nd ed No. of Copies : 1